Industrial Engineering, Machine Design and Automation (IEMDA 2014) and Computer Science and Application (CCSA 2014) proceedings of the 2014 Congress on IEMDA 2014 & proceedings of the 2nd Congress on CCSA 2014 : Sanya, Hainan, China, 12-14 Dec 2014 - Qin, Shihong; Li, Xiaolong 1977 November 19- (World Scientific, 2015)
This proceedings put together 68 selected articles from the joint conferences of 2014 Congress on Industrial Engineering, Machine Design and Automation (IEMDA2014) and the 2nd Congress on Computer Science and Application (CCSA2014), held in Sanya, China during December 12 - 14, 2014.The conference program of IEMDA 2014 focused on areas of Industrial Engineering, Machine Design and Automation, while the CCSA 2014 program provided the platform for Computer Science and Applications.Collected together the latest research results and applications on industrial engineering, machine design, automation, and computer science and other related Engineering topics. All submitted papers to this proceedings were subjected to strict peer-reviewing by 2 4 expert referees, to ensure that all articles selected are of highest standard and are relevance to the conference